On Methods and Strategies of Repertoire Rhetoric in the Presidential Inauguration Speech of Barack Obama and Donald Trump - Rida Nurlatifasari; M.R. Nababan; Riyadi Santosa; Tri Wiratno (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2022)
Abstract. Being the kernel of persuasive devices in a speech, methods and strategies of repertoire rhetoric ascertain the objective of the persuasion. They are unique and their exertion in an individual doing the persuasion may differ from one to another. This paper attempts to reveal the use of methods and strategies of repertoire rhetoric in the presidential inauguration speech of Barack Obama and Donald Trump. The objectives of the study cover the categorization of the strategies and methods of repertoire rhetoric employed by each of them and compare their strategies and methods of rhetoric to unravel the effectiveness of the persuasion in their presidential inauguration speech. This study is based on the qualitative paradigm resorting to multiple case study model. The sampling of data and data source are purposive. The research method implemented the principles of ethnography in terms of data collection and data analysis. The result of the study shows that both Obama and Trump resort to three different methods of rhetoric, with the same propensity towards pathos method. However, it is also found that Obama’s use of logos is almost as high as his use of pathos, leaving Trump’s logos far behind. Even so, the finding of Trump also resorting to logos is contradictory with the common and media belief that Trump solely employs pathos method in all of his remarks. In terms of strategies of rhetoric, both utilize a wide range of options with Obama tending to use syntactic devices and Trump opting for repetition mostly as expected. Keywords: repertoire rhetoric method, repertoire rhetoric strategies, Barack Obama, Donald Trump, presidential inauguration speechAbstrak. Karena menjadi bagian penting dalam alat persuasif dalam pidato politik, metode dan strategi repertoir retoris dapat memantapkan tujuan persuasi. Dua aspek tersebut bersifat unik dan penggunaannya pada masing-masing individu yang melakukan persuasi berbeda-beda. Artikel ini bertujuan untuk mengungkap penggunaan metode dan strategi retorik dalam pidato inaugurasi kepresidenan Barrack Obama dan Donald Trump. Tujuan penelitian mencakup pengategorian strategi dan metode repertoir retoris yang digunakan oleh keduanya dan membandingkan metode dan strategi masing-masing untuk mengungkap keefektifan persuasi dalam pidato inaugurasi tersebut. Penelitian ini menggunakan paradigma kualitatif yang berjenis model studi kasus ganda. Pengambilan sampel data dan sumber data bersifat purposif. Metode penelitian ini menerapkan prinsip-prinsip etnografi dalam pengumpulan dan analisis data. Hasil penelitian menunjukkan bahwa baik Obama maupun Trump menggunakan tiga metode retoris, dengan penekanan sama-sama pada metode pathos. Meskipun dmeikian, juga ditemukan dalam penelitian bahwa frekuensi penggunaan metode logos oleh Obama sama tingginya dengan penggunaan pathosnya, sedangkan Trump jarang menggunakan metode logos. Tetapi, hasil temuan yang mengungkap bahwa Trump juga memanfaatkan metode logos dalam pidatonya kontradiksi dengan kepercayaan umum dan media yang memandang Trump selalu menerapkan pathos saja dalam pidatonya. Dalam hal strategi retorik, keduanya menerapkan pilihan yang beragam dengan Obama lebih banyak menggunakan syntactic devices dan Trump sering menggunakan repetisi seperti yang sudah diduga.Kata kunci: metode repertoir retorik, strategi repertoir retorik, Barrack Obama, Donald Trump, pidato inaugurasi presiden